Pengaruh Pola Asuh dan Metode STIFin terhadap Hasil Belajar Pendidikan Karakter dalam Pembelajaran PKn Siswa Kelas IV SD - Mutiah, Tiah; Sardjijo; Warsihna, Jaka (Institut Agama Islam Negeri Palangka Raya, 2025)
This study investigates the influence of parenting styles and the STIFIn learning method on students' character education outcomes in Civics (PKn) classes at the fourth-grade level. The research employed a quantitative factorial experimental design (2x5) involving 30 students from SDIT Assuryaniyyah, Bekasi. The researchers categorized the sample based on parenting styles (democratic and permissive) and STIFIn personality types (Sensing, Thinking, Intuiting, Feeling, and Instinct). They collected the data through STIFIn tests, parenting style questionnaires, and final learning achievement scores. Using Two-Way ANOVA, the study found a significant main effect of parenting style on learning outcomes (F = 6.808, p = 0.017), with democratic parenting leading to higher scores (M = 89.13) than permissive parenting (M = 84.93). The main effect of the STIFIn type was also significant (F = 5.692, p = 0.003), with the highest scores among students with the Feeling type (M = 92.33). Moreover, a significant interaction was found between parenting style and STIFIn type (F = 3.596, p = 0.023), indicating that the effectiveness of parenting styles varies depending on students' personality types. These findings highlight the importance of aligning parenting approaches and personalized learning strategies based on student personality types to optimize character education outcomes.